Maqāṣid asy-Syarī'ah and Siyāsah Māliyah Analysis of the Free Nutritious Meal Program (MBG) Policy in Indonesia - Aria Roby Putra (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2026)
This study aims to analyze the maqāṣid al-sharī'ah and siyāsah māliyah in relation to the Free Nutritious Meals (MBG) Program policy in Indonesia. The research method used is normative legal research employing a legislative approach, a conceptual approach, and a maqāṣid al-sharī'ah approach. Legal materials were obtained through a literature review covering legislation, books, scholarly articles, and other relevant literature. The results indicate that the MBG Program constitutes a dharuriyyat need because it supports the protection of life, intellect, and lineage through the provision of sustainable nutrition. This finding reinforces the development of contemporary maqāṣid asy-syarī’ah literature, which interprets ḥifẓ an-nasl as no longer limited to the protection of lineage but also encompassing children’s quality of life, health, and well-being, and contextualizes it within the MBG policy as an innovative contribution to research. From the perspective of Islamic public economics, the program’s financing reflects the principles of siyāsah māliyah and al-‘Adālah al-Tawzi‘iyyah. However, the implementation of the MBG also has the potential to cause mafsadah if it is not supported by fiscal sustainability, food quality oversight, data integration, and community empowerment, thereby fostering dependence on state assistance. Therefore, the success of the MBG must be directed toward the realization of al-maṣlaḥah al-`āmmah through accountable, sustainable, and equitable governance.